Spatial gradients in trace metal concentrations in the surface microlayer of the Mediterranean Sea - Tovar-Sánchez, Antonio; Arrieta, Jesús M.; Duarte, Carlos M.; Sañudo-Wilhelmy, Sergio A. (Frontiers in Marine Science, 2014)
The relationship between dust deposition and surface water metal concentrations is poorly understood. Dissolution, solubility, and partitioning reactions of trace metals from dust particles are governed by complex chemical, biological, and physical processes occurring in the surface ocean. Despite that, the role of the sea surface microlayer (SML), a thin, but fundamental component modulating the air-sea exchange of materials has not been properly evaluated. Our study revealed that the SML of the Mediterranean Sea is enriched with bioactive trace metals (i.e., Cd, Co, Cu and Fe), ranging from 8 (for Cd) to 1000 (for Fe) times higher than the dissolved metal pool in the underlying water column. The highest enrichments were spatially correlated with the atmospheric deposition of mineral particles. Our mass balance results suggest that the SML in the Mediterranean Sea contains about 2 tonnes of Fe. However, we did not detect any trends between the concentrations of metals in SML with the subsurface water concentrations and biomass distributions. These findings suggest that future studies are needed to quantify the rate of metal exchange between the SML and the bioavailable pool and that the SML should be considered to better understand the effect of atmospheric inputs on the biogeochemistry of trace metals in the ocean.